KONTRIBUSI MATA KULIAH BAHASA INDONESIA TERHADAP PENGEMBANGAN KEMAMPUAN KOMUNIKASI AKADEMIK MAHASISWA - Nova Mustika (EDU RESEARCH, 2024)
This study analyzes the role of the Indonesian Language Course in developing students' academic communication skills in higher education, focusing on identifying teaching challenges and evaluating instructional methods. Using a descriptive quantitative approach, data were collected through questionnaires and interviews with 120 students. The findings reveal that this course significantly contributes to improving students' formal writing and speaking skills, particularly in academic and professional contexts. However, challenges remain in terms of material relevance, lecture-dominated teaching methods, and limited use of technology. Recommendations include integrating technology, adjusting the curriculum, and applying interactive teaching methods to enhance instructional effectiveness. These findings provide insights into strategies for developing relevant Indonesian language learning in the digital era